The Impact Of Spotify Advertisements On Free Accounts To Purchase Decisions For Spotify Premium Accounts With Consumer Attitudes As The Mediating Variable - Jane Evelyn Alodia; Annisa Rahmani Qastharin (Journal Integration of Management Studies, 2024)
In recent years, digital music streaming services have increasingly relied on advertisements to generate revenue and encourage users to upgrade to premium accounts. Previous research has shown that effective advertising can significantly influence consumer attitudes and purchasing decisions. However, advertisements may also provoke negative reactions such as annoyance and irritation, potentially impacting user experience. This study examines the impact of Spotify advertisements on consumers' purchasing decisions to upgrade from free to premium accounts, with consumer attitude as a mediating variable. This study used a quantitative approach to collect data from an online survey of 399 Spotify users. Data analysis was conducted using descriptive statistics and partial least squares structural equation modeling (PLS-SEM). The results indicate that advertising significantly enhances customer attitudes and positively influences purchase decisions. Furthermore, advertisements impact purchase decisions indirectly through customer attitudes. Despite these positive effects, the study also reveals that advertisements can cause adverse reactions, such as annoyance and irritation. Respondent feedback highlights ad content, frequency, and timing issues, which often disrupt the user experience. These findings provide valuable insights for digital marketers and advertisers seeking to optimize their campaigns on platforms like Spotify. Additionally, this research contributes to the broader understanding of advertising effectiveness, customer behavior, and digital marketing strategies in the context of music streaming services.